Determination of Obese Protein Concentration in a Biological Sample - Šaćira Mandal (Kemija u Industriji)
Adipose tissue is a metabolically active organ with both endocrine and paracrine functions. It secretes a number of cytokines (adipocytokines) that play critical roles in the development of metabolic diseases and inflammation. Previous studies have shown that the product of an obese protein (leptin), a hormone secreted by adipose tissue, is associated with obesity, type 2 diabetes mellitus (T2D), and dyslipidaemia. Moreover, leptin has been identified as a potential and valuable therapeutic molecule for the treatment of glycaemia, dyslipidaemia, and T2D. The aim of this study was to analyse the concentration of obesity protein as an adipocytokine in a population from Sarajevo, Bosnia and Herzegovina. The study included 26 participants: 13 healthy subjects as the control group, and 13 untreated diabetics. Biochemical parameter, such as glucose, glycated haemoglobin, lipid profile, and concentrations of the hormones leptin and insulin were analysed. Biochemical parameters were determined using standard IFCC methods, while leptin and insulin concentrations were analysed using an ELISA assay. The measured concentration of obesity protein in plasma was significantly higher (p < 0.001) in diabetics compared to healthy subjects, with females exhibiting higher leptin levels than males in both groups. Significant differences in concentrations of biochemical characteristics between the diabetic and control groups (p < 0.001 and p < 0.05 respectively) were also observed, with elevated values noted particularly in females. These results suggest that leptin can serve as a biomarker for glucose and lipid regulation in untreated diabetic patients.